Lupus Enteritis: An Unusual Flare of Systemic Lupus Erythematosus - Casanova Pinto, J; Costa, MG; Fernandes, B; Ramalheira, C (My University, 2025)
A woman in her 20s with previously diagnosed systemic lupus erythematosus (SLE) presented with a year-long history of chronic watery diarrhea, significant weight loss, and additive symmetrical inflammatory polyarthritis. She had been receiving hydroxychloroquine, azathioprine, and low-dose prednisolone but had discontinued treatment shortly before admission due to persistent vomiting. Laboratory evaluation showed new-onset proteinuria, hypokalemia, hypomagnesemia, microcytic anemia, lymphopenia, low complement levels, and markedly elevated antinuclear and anti-double-stranded deoxyribonucleic acid (anti-dsDNA) antibodies. Imaging demonstrated diffuse mural thickening and submucosal edema of the small bowel, a large left pleural effusion, and peritoneal fluid. The patient was treated with intravenous methylprednisolone pulses, followed by high-dose oral prednisolone and hydroxychloroquine. Renal biopsy revealed class III lupus nephritis, leading to the initiation of mycophenolate mofetil (MMF). Under this immunosuppressive regimen, gastrointestinal symptoms resolved, pleural effusion regressed, and renal parameters progressively improved. This case illustrates lupus enteritis as a rare but clinically significant manifestation of SLE, presenting with chronic diarrhea in association with other systemic features, including inflammatory polyarthritis, hematological involvement, and lupus nephritis. This report emphasizes the importance of considering lupus enteritis in patients with SLE who present with persistent gastrointestinal symptoms and of early recognition and prompt initiation of appropriate immunosuppressive therapy to prevent severe complications such as ischemia and perforation.